Объяснение:
1) f(x)=2e^x+3x² f'(x)=2e^x+6x
2) f(x)= x sinx. f'(x)= sinx+xcosx
3) у = (3х – 1)(2 – х) y'=3(2 – х)+(3х – 1)×(-1)=6-3x-3x+1=-6x+7
4) y=9x²-cosx y'= 18x+sinx
5) y=e^x-x^7 y'= e^x-7x^6
7) f '(1), f(x)=3x2-2x+1. f'(x)=6x-2; f'(1)=6-2=4
8) у = х²(3х^5 – 2) ; х0 = – 1. у' =(3x^7-2x²)'=21x^6-4x
y'(-1)=21+4=25
9) f '( ), f(x)=(2x-1)cosx=2cosx-(2x-1)sinx
10) f '(1), f(x)=(3-x²)(x²+6)= -2x(x²+6)+2x(3-x²) = -4x³ -6x
11) f '(1), f(x)=(x^4-3)(x²+2), f'(x)=3x³ (x²+2)+2x(x^4-3)=5x^5+6x³-6x
Объяснение:
{7у−х=5;
4х+5у=2.
Домножим первое на 4 ;
28y-4x=20
4x+5y=2
Сложение:
28y-4x+4x+5y=20+2
33y=22
y=2/3
Подставим:
4x+5y=2
4x+5*2/3=2
4x+10/3=2
4x=-4/3
x= -1/3
(-1/3;2/3)
2)
10х+7у=−2
5у−2х=19.6
Домножим второе на 5:
10х+7у=−2
25y-10x=98
10х+7у+25y-10x=96
32y=96
y=3
Подставим:
75-10x=98
-10x=23
x=-23/10
x=-2.3
(-2.3;3)
3)
5(х−5)−3у=4у−4
6х=3(у−8)+60
5x-25-3y-4y+4=0
3y-24+60-6x=0
5x-7y-21=0
3y-6x+36=0
5x-7y=21
3y-6x=-36
Домножим:
30x-42y=126
15y-30x=-180
30x-42y+15y-30x=126+(-180)
-27y=-54
y=2
5x-7y=21
5x-14=21
5x=35
x=7
(2;7)
2х + 37− 5у − 12=1
3у+х=12
2x-5y+24=0
3y+x=12
2x-5y=-24
3y+x=12
Домножим:
2x-5y=-24
-6y-2x=-24
Сложение;
2x-5y-6y-2x=-24+(-24)
-11y=-48
y=48/11
Подставим y:
3y+x=12
3*48/11+x=12
144/11+x=12
x=12-144/11
x=-11/12
48/11=4 4/11
(-11/12 ; 4 4/11)
5 * ( X - 1 ) ≥ 4 * ( 2 + X )
5X - 5 ≥ 8 + 4X
5X - 4X ≥ 8 + 5
X ≥ 13
ответ [ 13 ; + бесконечность )